Physical activity and prevalence of overweight and obesity in adolescent students 12 to 18 years of the city of Juliaca 2015 - Flores Paredes, Alcides (2017)
The research on the general objective, to determine the relationship between physical activity and the prevalence of overweight and obesity in school adolescents aged 12 to 18 years in the city of Juliaca 2015, the type of basic research, A sample of probabilistic type Of 1488 students from a population of 4813 students (ladies and men) in grades 1 through 5; Of the Secondary Public Educational Institutions: Commerce No. 32, "Peru Birf", "Jose Antonio Encinas", and Polytechnic "Los Andes" of the city of Juliaca. The research was carried out during the months of April to August of the year 2015. The results show that there is a low association of the prevalence of overweight with physical activity, finding a correlation of 0.002 being non-significant (sig.> 0,05). Regarding obesity, we found an inversely proportional association of -0.0183 being non-significant (sig.> 0,05). The protective role of physical activity was determined by obtaining an inversely proportional correlation between physical activity and the prevalence of overweight and obesity in school adolescents aged 12 to 18 years. We conclude that there are 60 women who are overweight with 53.6% and 20 women of students who are on the obesity scale, representing 69.0% of a total of 774 female students. In the male schoolchildren there are 52 students in the overweight scale, representing 46.4% and 9 students with obesity, representing 31.0% of a total of 714 males.